Allometry relationship of mangrove horseshoe crab, carcinoscorpius rotundicauda from the west coast of Peninsular Malaysia - Ni, Syuhaida; Mohamed, Rozihan; John, Akbar; MS, Akmal; HD, Joni (AkiNik Publications, 2019)
Carcinoscorpius rotundicauda is mangrove horseshoe crab that inhabit in mudflats ecosystem. The values information on morphometric variability of C. rotundicauda is still limited especially along west coast of Peninsular Malaysia. A total of 148 samples of C. rotundicauda were collected randomly from Merlimau, Melaka and Pendas, Johor characterized by different environmental conditions in order to study the intraspecific variations using allometry relationship. Body weight for male C. rotundicauda was 80.02±21.71 g and female was 141.17±54.56 g in Merlimau while in Pendas, the mean for body weight in male was 110.78±39.27 g and female was 177.05±70.98 g. All morphometric parameter were converted into logarithmic value as allometric growth analysis. An isometric allometry growth (b=3) was recorded in the relationship between length-weight for female in Pendas and width-weight for female in Merlimau population. The length/width-length relationships were recorded as an isometric growth (b=1) except for width-length and length-length relationships of male in both population. Overall performance showed that increment in all body parts of female C. rotundicauda showed better growth than males. Follow up study on the relationship of horseshoe crab population growth are needed in developing strategies on monitoring, conservation and breeding of horseshoe crab.